Intencjolalnyj stil’: psychičeskie i komunikativnye scenarii - Duskaeva, Liliâ R. (Stylistyka, 2020)
This article shows how mental activity is reflected in the intentional style and specific communication scripts. This analysis shows the cognitive mechanisms and possibilities of the language. Tools of different language levels of several semantic groups help to convey communicative action. These tools reflect perception, speech and thought, performing (dance) actions. Time means reflect the dynamics of what is happening.